Analysis of Indus Delta Groundwater and Surface water Suitability for Domestic and Irrigation Purposes - Ghulam Shabir Solangi; Altaf Ali Siyal; Pirah Siyal (Civil Engineering Journal, 2019)
The present study was conducted to analyze the suitability of groundwater and surface water of the Indus Delta, Pakistan for domestic and irrigation purposes based on the concentrations of arsenic (As), total dissolved solids (TDS), and chloride (Cl). Around 180 georeferenced groundwater and 50 surface water samples randomly collected were analyzed and mapped spatially using ArcGIS 10.5 software. The results were compared with their respective WHO and FAO guidelines. The analysis revealed that as in groundwater and surface water samples ranged up to 200, and 25 µg/L respectively. Similarly, the TDS in the groundwater and surface water ranged from 203 to 17, 664 mg/L and 378 to 38,272 mg/L respectively. The Cl in groundwater and surface water varied between 131 and 6,275 mg/L and 440 to 17,406 mg/L respectively. Overall, about 18%, 87% and 94% of the groundwater, and 10%, 92% and 56% of the surface waters possessed higher concentrations of As, TDS, and Cl, respectively. The higher levels of Cl in the samples are attributed to subsurface seawater intrusion in the delta. Analysis results and GIS mapping of water quality parameters revealed that in most of the delta, the quality of water was not suitable for drinking and agricultural purposes, thus should be properly treated before its use.